2019
DOI: 10.1007/s00603-019-01934-1
|View full text |Cite
|
Sign up to set email alerts
|

From Static to Dynamic Stiffness of Shales: Frequency and Stress Dependence

Abstract: The relation between static and dynamic stiffness in shales is important for many engineering applications. Dynamic stiffness, calculated from wave velocities, is often related to static stiffness through simple empirical correlations. The reason for this is that dynamic properties are often easier to obtain; however, it is the static properties that define the actual subsurface response to stress or pore pressure changes. Rocks are not elastic media, and stiffness depends on the stress state, stress-change am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Although the dispersion of Young's modulus has been mentioned in literature [14,16,17], it has not been supported by robust experimental data or mathematical models. Therefore, our studies may facilitate the development of modelling the dynamic characteristics of clastic rocks.…”
Section: Closing Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the dispersion of Young's modulus has been mentioned in literature [14,16,17], it has not been supported by robust experimental data or mathematical models. Therefore, our studies may facilitate the development of modelling the dynamic characteristics of clastic rocks.…”
Section: Closing Remarksmentioning
confidence: 99%
“…[13]) reported that Young's moduli of Navajo sandstone, Spergen limestone and Oklahoma granite are independent of the frequency of dynamic loading at the strain below 10 −7 in the frequency range from 4 to 400 Hz. Recent studies on Opalinus Clay (see [14]) and Mancos shale (see [15]) demonstrated an increase in Young's modulus and a decrease in Poisson's ratio with an increase in frequency of the dynamic loading from 1 to 100 Hz at the strain around 10 −6 . The authors [16] showed that with an increase in frequency from 1 to 50 Hz for samples with a strain range between 10 −8 and 10 −6 , both Young's modulus and Poisson's ratio of Donnybrook sandstone increase, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…9, (dε ax /dσ ax ) 0 0.20 GPa −1 , and C 9×10 −5 MPa −2 . Lozovyi et al (2018) have shown that the equation (10) can be used to model the non-elastic effects in both axial and radial strains, ε ax and ε rad , as function of axial stress change, σ ax . This allows for finding zero-stress extrapolated Young's moduli and Poisson's ratios.…”
Section: Static Stiffness -Non-elastic Effectsmentioning
confidence: 99%
“…The model is based on the empirical finding that the rock compressibility increases linearly with stress amplitude. Some rocks, especially shales, exhibit relatively large stiffness dispersion (Duranti, Ewy and Hofmann 2005;Hofmann 2006;Tutuncu 2010;Szewczyk, Bauer and Holt 2016;Lozovyi et al 2018). Quasi-static rock deformations in static tests are usually done with loading rates that correspond to average loading rates of dynamic measurements in the sub-hertz frequency regime.…”
Section: Introductionmentioning
confidence: 99%
“…Stress fields are correlated with stress indicators, such as seismic velocity. Previous studies have shown a significant non-linear increase in seismic velocities with a small rise in the hydrostatic pressure (Mayr and Burkhardt 2006;Lozovyi and Bauer 2019). Additionally, similar studies showed that the increase in velocity is limited once the change in pressure exceeds a certain threshold (Mavko et al 2009;Mavko et al 2009).…”
Section: Introductionmentioning
confidence: 91%